Controlled Reduction of Nitriles by Sodium Hydride and Zinc Chloride - Ong, Derek Yiren; Chiba, Shunsuke (Synthesis, 2020)
A new protocol for the controlled reduction of nitriles to aldehydes was developed using a combination of sodium hydride and zinc chloride. The iminyl zinc intermediates derived from aromatic nitriles could be further functionalized with allylmetal nucleophiles to afford homoallylamines. As the method allows the reduction of various aliphatic and aromatic nitriles with a concise procedure under milder reaction conditions and exhibits wide functional group compatibility, it is well suited for use in various opportunities in chemical synthesis.
Keywords: nitriles; aldehydes; sodium hydride; zinc chloride; reduction